Detection and Establishment of Aedes notoscriptus (Diptera: Culicidae) Mosquitoes in Southern California, United States. Issue 1 (7th October 2021) - Metzger, Marco E; Wekesa, J Wakoli; Kluh, Susanne; Fujioka, Kenn K; Saviskas, Robert; Arugay, Aaron; McConnell, Nathan; Nguyen, Kiet; Krueger, Laura; Hacker, Gregory M; Hu, Renjie; Kramer, Vicki L
Abstract: Aedes notoscriptus (Skuse), the Australian backyard mosquito, is a pestiferous daytime-biting species native to Australia and the surrounding southwestern Pacific region. It is suspected to play a role in the transmission of several arboviruses and is considered a competent vector of dog heartworm, Dirofilaria immitis (Leidy). This highly adaptable mosquito thrives in natural and artificial water-holding containers in both forested and urbanized areas, from tropical to temperate climates, and has benefitted from a close association with humans, increasing in abundance within its native range. It invaded and successfully established in New Zealand as well as in previously unoccupied temperate and arid regions of Australia. Ae. notoscriptus was discovered in Los Angeles County, CA, in 2014, marking the first time this species had been found outside the southwestern Pacific region. By the end of 2019, immature and adult mosquitoes had been collected from 364 unique locations within 44 cities spanning three southern California counties. The discovery, establishment, and rapid spread of this species in urban areas may signal the global movement and advent of a new invasive container-inhabiting species. The biting nuisance, public health, and veterinary health implications associated with the invasion of southern California by this mosquito are discussed.